Polin : Jews and the Emerging Polish State. - Polonsky, Antony (Polin Studies in Polish Jewry Ser., 2008)
Polin' is a forum for historical and cultural material on Polish and East European Jewry. Each volume contains articles representing original research, often including previously unpublished documents, and a review essay section.